Censorship in book selection of sectarian private high school libraries in the city of San Fernando, Pampanga - Escober, Diana Abigail T. (2009)
This study was based on the study conducted by Fairlyn Haduca (2005) which was based on the issue of book censorship against book selection standards and library practices in the library.